THE IMPACT OF PUBLIC-PRIVATE PARTNERSHIP ON EMPLOYMENT: AN ECONOMIC ANALYSIS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article examines how public-private partnership (PPP) mechanisms influence job creation, changes in the structure of employment, and the quality of labor. It also analyzes the impact of PPPs on employment in developed countries, using the examples of the United States, European Union member states, Japan, and Canada.
Keywords: public-private partnership, employment, labor market, infrastructure projects, government policy, socio-economic development.